Cryptogenic and non-cryptogenic liver abscess: A retrospective analysis of 178 cases revealed distinct characteristics. Issue 9 (September 2018) - Chen, Jing; Zhang, Minwei; Chen, Jinlong; Ning, Yaogui; Cai, Xiaoyang; Zhang, Li; Xu, Hao; Guo, Jing
Objective: To enhance theoretical support of pyogenic liver abscess (PLA) treatment by comparing characteristics of patients with either PLA with an identified infectious origin (non-cryptogenic) or PLA with no obvious underlying cause (cryptogenic). Methods: This retrospective study included all first episodes of PLA in adults admitted to a tertiary hospital between 2009 and 2016. Relevant clinical data were collected for patients with cryptogenic or non-cryptogenic PLA and compared across a number of characteristics. Results: In all, 178 patients were included: 111 cases (62.4%) of cryptogenic PLA, and 67 cases (37.6%) of non-cryptogenic PLA. Diabetes mellitus was significantly more prevalent in patients with cryptogenic PLA than those with non-cryptogenic PLA. The proportion of multidrug resistance/poly-microbial infection was significantly lower and Klebsiella pneumoniae infection was significantly higher in the cryptogenic versus non-cryptogenic PLA group. Metastatic infection occurred in four patients with cryptogenic PLA only, and all had diabetes and K. pneumoniae infection. Multivariate logistic regression analysis revealed that male sex, diabetes and K. pneumoniae were independent predictors for cryptogenic PLA. Conclusions: Cryptogenic and non-cryptogenic PLA have distinctly different characteristics, suggesting a potential need for different treatment approaches.